Serial kasus pneumonia neonatal dengan kemungkinan transmisi vertikal SARS-CoV-2 pada masa kehamilan - Ida Ayu Sri Kusuma Dewi; Ade Tsarina Indira (Intisari Sains Medis, 2022)
Background: The vertical transmission of SARS-CoV-2 from pregnant women to fetuses during pregnancy is still under debate. However, the incidence of COVID-19 in neonates born to mothers with SARS-Cov-2 infection is increasing. Several case reports suspect that the possibility of transmission of SARS-CoV-2 can occur vertically through the placenta. Most neonates with COVID-19 infection experience mild illness, but some develop severe symptoms.Case Report: We report two cases of neonates with Neonatal Pneumonia born to mothers with COVID-19 infection. The first case is a baby born to a mother infected with COVID-19 with placenta previa totalis. The baby was born with severe asphyxia. The second case was a baby born to a mother infected with COVID-19 with premature membrane rupture. The baby experiences respiratory distress after four days of age. An RT-PCR swab examination was performed in both cases, and the results were positive. After intensive care, both babies were discharged in stable condition.Conclusion: The vertical transmission of SARS-CoV-2 is still under debate. Examinations other than nasopharyngeal RT-PCR swabs such as peripheral blood examinations for mother and baby, placenta, umbilical cord, umbilical cord blood, amniotic fluid are needed to support vertical transmission. In this case report, we could only perform the Nasopharyngeal RT-PCR swab test due to various limitations. Latar Belakang: Transmisi vertical SARS-CoV-2 dari ibu hamil ke janin selama masa kehamilan masih dalam perdebatan. Namun Angka kejadian COVID-19 pada neonatus yang lahir dari ibu dengan infeksi SARS-Cov-2 tersebut kian meningkat. Beberapa laporan kasus mencurigai bahwa kemungkinan transmisi dari SARS-CoV-2 dapat terjadi secara vertikal melalui plasenta. Sebagian besar neonatus dengan infeksi COVID-19 ini mengalami gejala ringan, namun beberapa berkembang menjadi berat. Laporan Kasus: Pada laporan ini, kami melaporkan dua kasus neonatus dengan pneumonia neonatal yang lahir dari ibu dengan infeksi COVID-19. Kasus pertama merupakan bayi yang lahir dari ibu yang terinfeksi COVID-19 dengan plasenta previa totalis, bayi lahir dengan asfiksia berat. Kasus kedua merupakan bayi yang lahir dari ibu yang terinfeksi COVID-19 dengan ketuban pecah dini (KPD), bayi mengalami distress napas setelah usia 4 hari. Pada kedua kasus ini dilakukan pemeriksaan swab RT-PCR dan mendapatkan hasil positif. Setelah dilakukan perawatan intensif, kedua bayi dipulangkan dengan kondisi stabil. Kesimpulan: Transmisi vertikal SARS-CoV-2 masih dalam perdebatan. Pemeriksaan selain swab RT-PCR nasofaring seperti pemeriksaan darah perifer pada ibu dan bayi, plasenta, tali pusat, darah tali pusat, cairanan amnion dibutuhkan untuk menunjang adanya suatu transmisi vertikal. Pada laporan kasus ini kami hanya dapat melakukan tes swab RT-PCR nasofaring dikarenakan keterbatasan pemeriksaan.